Filmische Seitenblicke Cinepoetische Exkursionen ins Kino von 1968 - Kappelhoff, Hermann; Lötscher, Christine; Illger, Daniel (Cinepoetics, 2018)
Did 1968 fail? The question is misstated. For the significance and consequences of '68 cannot be captured in a coherent narrative. That year appears as the point of culmination of a set of highly heterogeneous cultural, social, and political phenomena. Cinema, with its classics and gems to be (re-)discovered, proves to be a kaleidoscope that lets us perceive the fractures and contradictions of '68.